2006
DOI: 10.1161/01.str.0000204223.04182.4a
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Chlamydia pneumoniae Infection and Stroke in Cameroon

Abstract: Background and Purpose-To determine the relationship between chronic Chlamydia pneumoniae infection and stroke in Cameroon. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…They found that positive serum IgG and IgA antibody titer by microimmunofluorescence (MIF) test, against C. pneumoniae was significantly more in ischemic stroke patients compared to age and sex matched control subjects [8,9]. This is in agreement with previous studies where C. pneumoniae antibody positivity has been noted in young stroke patients [3,47].…”
Section: Stroke An Immunopathogenic Complication Of Persistent C Pnsupporting
confidence: 86%
See 1 more Smart Citation
“…They found that positive serum IgG and IgA antibody titer by microimmunofluorescence (MIF) test, against C. pneumoniae was significantly more in ischemic stroke patients compared to age and sex matched control subjects [8,9]. This is in agreement with previous studies where C. pneumoniae antibody positivity has been noted in young stroke patients [3,47].…”
Section: Stroke An Immunopathogenic Complication Of Persistent C Pnsupporting
confidence: 86%
“…In Cameroon, Njamnshi AK et al demonstrated that C. pneumoniae infection is significantly associated with ischemic stroke in patients in the < 50 years age group compared to matched www.intechopen.com controls [47]. Another study also demonstrated that C. pneumoniae seropositivity can increase the risk of stroke in young patients aged below 55 years in which, C. pneumoniae seropositivity in all ischemic stroke subgroups except stroke of indeterminate etiology is found [8].…”
Section: Stroke An Immunopathogenic Complication Of Persistent C Pnmentioning
confidence: 98%
“…In Cameroon, some studies have been carried on patients in the intensive care units [7] [8], sickle cell children [4] [6] and on risk factors of stroke [5] [10]. The only study that employed modern imaging technique (CT or MRI) is that of Chiasseu and Mbahe [9] although it looked mainly at less severe stroke in a small sample and very little information was reported on stroke subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In Medrano's study, there was no relationship between IgG antibodies against C. pneumoniae and cerebrovascular accidents (18). In another study in Cameroon, 64% of the patients with ischemic stroke had IgG against C. pneumoniae, compared to 55% positivity in the control group, the difference of which was not statistically significant (7).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, inflammation has been postulated to play an important role in initiation and development of atherosclerosis. Retrospective and cross-sectional studies have suggested that both bacterial and viral infections may be risk factors for atherosclerosis, ischemic stroke and acute coronary events (7)(8)(9)(10)(11). Some studies do not confirm the association between seropositivity to C. pneumoniae and increased risk of cardiovascular diseases in populations with stroke (12).…”
Section: Introductionmentioning
confidence: 99%